Safety assessment of molecular targeted therapies in association with radiotherapy in metastatic renal cell carcinoma: a real-life report. Issue 5 (June 2016) - Langrand-Escure, Julien; Vallard, Alexis; Rivoirard, Romain; Méry, Benoîte; Guy, Jean-Baptiste; Espenel, Sophie; Trone, Jane-Chloé; Ben Mrad, Majed; Diao, Peng; Rancoule, Chloé; Suchaud, Jean-Philippe; Fournel, Pierre; et al.
Abstract : Molecular targeted therapies (TT) are the cornerstone of metastatic renal cell carcinoma (RCC) treatment. There is a paucity of data on the safety of the radiotherapy (RT)–TT association in a sequential or a concomitant setting. The aim of the present study is to retrospectively assess the safety of the RT–TT association. From 2006 to 2014, data from 84 consecutive patients treated with RT and TT for metastatic RCC were retrospectively collected. RT–TT sequential and concomitant associations were, respectively, defined by a time interval of more than five TT half-lives and less than or equal to five TT half-lives between the last TT administration and RT initiation. Toxicities in the fields of RT were assessed systematically. As many patients received several TT and RT courses, 136 RT–TT associations were analyzed, with 66 sequential and 70 concomitant schemes. RT was mainly delivered on bone (75%) and brain metastases (14.7%). TT were tyrosine kinase inhibitors (73.5%), mTOR inhibitors (19.8%), and monoclonal antibodies (6.7%). With a median follow-up of 9.5 months, whatever the sequence, no grade≥4 toxicity was reported. Two grade 3 toxicities were reported with sequential (3%) and concomitant (2.9%) RT–TT, respectively. Sequential or concomitant RT–TT associations in metastatic RCC do not seem to cause major toxicity.